Iraklı Şeyh Abdülkerim el-Müderris yorumlama metodolojisi - Mahmood, Nadhim Muhammed (My University, 2021)
Bu çalışma, çağdaş Iraklı müfessir Şeyh Abdülkerim el-Müderris’in (1904-2005) Mevâhibu’r-Rahmân fî tefsîri’l-Kurân adlı tefsirindeki tefsir metodunu ele almaktadır. Bu tefsir, ifade kolaylığı ile seçkinleşmiş, yapaylık ve karmaşıklıktan uzaktır. Tefsir yedi cilt olarak basılmıştır. Bu çalışma, bilimsel araştırma alanında bilinen metodoloji ve araştırma ilkelerine göre yazılmıştır. Tümevarım ve tanımlayıcı yöntemin yanı sıra, analitik ve eleştirel yönteme dayanmıştır. Çalışmamız üç bölüm ve bir sonuçtan oluşur. Tezin birinci bölümünde Şeyh el-Müderris’i tanıttık. Şahsi ve ilmi hayatı, eserleri ve hocalarını sunduk. Hayatı boyunca; hoca, imam, hatip ve müftü olarak yaptığı tüm görevleri anlattık. İkinci bölümünde ise, tefsir kitabını ele alıp, eserin yazımı sırasında izlediği yöntemi ve başvurduğu en önemli kaynakları inceledik. Çalışmanın üçüncü bölümüne gelince, Şeyh el-Müderris’in rivayet ve dirayet tefsirinde izlediği yöntemi açıkladık. İsrâiliyata yaklaşımını inceledik. Daha sonra tefsirinin bilimsel değerinden bahsettik.

This study deals with the approach of Sheikh Abdul Karim Almadres in his interpretation named (Rahman'sgiftsin the interpretation of the Quran), he is a contemporary Iraqi interpreter, leaving to us an interpretation with a simplified explanation of the phrase, and away from the baroque and complex. and the interpretations printed and is composed of seven volumes, and the study was according to methodology and research assets known in the field of scientific research, where it adopted by the inductive approach and the descriptive and analytical and critical approach. This study came to study in three chapters and a conclusion, in the first chapter, the researcher definition Sheikh Almadres who lived between the period (1904 - 2005AD), and subjected to his personal life, scientific, and his writings and elderly, the most important positions held, as a teacher and an imam and preacher and Mufti. In the second chapter was a researcher for the definition of interpretation, and the way they pursued it, and the most important sources, which adopted it, the researcher, clarify the way of Sheikh in interpretation by Mathur, and interpretation by opinion, and his position on Israeli, and in the researcher expose the issues Quranic sciences, as reasons of godown and Mecci and Madani, and his opinions in cases of different miracles of the Qur'an, and in, the researcher showed in this study care of Almadres about the science of Arab language and the exchange and eloquent v pieces of poetry, and in Chapter three the researcher viewed the Almadres’sopinion on different matters of faith from the names and attributes, issues of fate and much, The acts of the people and the will and the equator, vision, and others. As the researcher which is the last one, the Almadres’theological issues both on the side of transactions or worships. At the end of the study was the conclusion, and which sum up the find in grand ideas, and was the most important attempt to define the scholars and researchers charismatic of Sheik Abdul Karim Almadres, and shed light on his interpretation, the statement of his approach, and highlight his scientific value, an opportunity to demonstrate the extent and status of the interpreter. He is best to protect and advocate, asking the God Almighty that has to grant success to me and helped me and paid my fault.
Keywords: Al-Mudarris; Hermeneutics; Irak; Iraq; Islam; İslam; Şeyh Abdulkerim el-müdrris; Tefsir; Tefsir bilimi; theological issues